Developing STEAM-based Interactive E-Modules with Religious Integration to Enhance Students’ Mathematical Literacy - Della Pitriani Putri; Agus Hikmat Syaf; T. Tutut Widiastuti A (Jurnal Pendidikan Matematika (JPM), 2025)
In the digital era, the challenge of learning lies not only in the delivery of material, but also in how the material is packaged to be meaningful and relevant to students. The use of technology in education, combined with STEAM (Science, Technology, Engineering, Arts, Mathematics) learning with the integration of religious values to improve mathematical literacy, is a potential strategy to improve the quality of student understanding, especially in mathematics learning. Therefore, this study aims to develop and assess the feasibility of a STEAM-based interactive e-module with the integration of religious values to improve students' mathematical literacy in statistics material. The research method used was Research and Development (R&D) with the ADDIE development model. The validation results showed that the developed interactive e-module was highly valid, with a score of 92.94% from media experts and 92.86% from material experts. In terms of practicality, student responses resulted in a score of 88.66% in the small-scale trial and 81.04% in the large-scale trial, both categorized as highly practical. Regarding effectiveness, the module achieved an effectiveness score of 76% in the small-scale trial and 88% in the large-scale trial. Furthermore, the effect size analysis showed a value of 0.7 in the small-scale trial and 1.2 in the large-scale trial, indicating a substantial increase in students' mathematical literacy. Thus, the findings suggest that the developed e-module is valid, practical, and effective for use as an interactive, innovative, and contextual mathematics learning medium that integrates religious values.